2013
DOI: 10.1371/journal.pone.0072634
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Diarrhoegenic Intestinal Parasite Infections among Non-ART HIV Patients in Fitche Hospital, Ethiopia

Abstract: BackgroundHIV infection has been modifying both the epidemiology and outcome of parasite infections. Hence, this study was undertaken to determine the prevalence of Cryptosporidium and other intestinal parasite infections among HIV positives with and without Antiretroviral Treatment(ART) and its association with CD4+ T-cell count.MethodsA cross-sectional study was conducted at Fitche hospital focusing on HIV positives who came to hospital for follow-ups. A total of 378 HIV positive persons with and without ART… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
37
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 21 publications
7
37
2
1
Order By: Relevance
“…Some studies reported that the improved immune system could reduce Blastocystis infection among HIV-infected children who were on antiretroviral treatment when compared with those who did not receive the antiretroviral therapy. 27,28 In our study, the prevalence of Blastocystis infection among HIV-infected children was significantly lower than among those HIV negatives, which was consistent with other studies from China 29 and Tanzania. 30,31 There is no evidence that either antiretroviral drugs or co-trimoxazole can prevent Blastocystis infection.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies reported that the improved immune system could reduce Blastocystis infection among HIV-infected children who were on antiretroviral treatment when compared with those who did not receive the antiretroviral therapy. 27,28 In our study, the prevalence of Blastocystis infection among HIV-infected children was significantly lower than among those HIV negatives, which was consistent with other studies from China 29 and Tanzania. 30,31 There is no evidence that either antiretroviral drugs or co-trimoxazole can prevent Blastocystis infection.…”
Section: Discussionsupporting
confidence: 92%
“…It was estimated that 60% of people worldwide were infected with intestinal parasites (1,2). Recent estimates indicate that at least more than one-quarter of the world's population are infected with intestinal parasites and most of them are people who live in developing countries (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1980s, waterborne protozoan parasites have emerged and re-emerged and became a worldwide public health problem, especially among vulnerable population groups (1) (2) . For example, children with a suppressed immune system are more susceptible to infections that are caused by opportunistic agents, especially when their CD4 + T-lymphocyte counts are <200 cells/mm 3 or 15%…”
mentioning
confidence: 99%
“…Monitoring HIV-infected children who are undergoing continuous ART in specialized units can ensure that acute parasitic infections remain asymptomatic in these children (1) . Furthermore, continuous contact between these children and parasites and/or environmental exposure to asymptomatic parasite genotypes may cause asymptomatic infections (9) .…”
mentioning
confidence: 99%
See 1 more Smart Citation